Mutations in cell division cycle genes CDC36 and CDC39 activate the Saccharomyces cerevisiae mating pheromone response pathway. - de Barros Lopes, M (1990)
Conditional mutations in the genes CDC36 and CDC39 cause arrest in the G1 phase of the Saccharomyces cerevisiae cell cycle at the restrictive temperature. We present evidence that this arrest is a consequence of a mutational activation of the mating pheromone response. cdc36 and cdc39 mutants expressed pheromone-inducible genes in the absence of pheromone and conjugated in the absence of a mating pheromone receptor. On the other hand, cells lacking the G beta subunit or overproducing the G alpha subunit of the transducing G protein that couples the receptor to the pheromone response pathway prevented constitutive activation of the pathway in cdc36 and cdc39 mutants. These epistasis relationships imply that the CDC36 and CDC39 gene products act at the level of the transducing G protein. The CDC36 and CDC39 gene products have a role in cellular processes other than the mating pheromone response. A mating-type heterozygous diploid cell, homozygous for either the cdc36 or cdc39 mutation, does not exhibit the G1 arrest phenotype but arrests asynchronously with respect to the cell cycle. A similar asynchronous arrest was observed in cdc36 and cdc39 cells where the pheromone response pathway had been inactivated by mutations in the transducing G protein. Furthermore, cdc36 and cdc39 mutants, when grown on carbon catabolite-derepressing medium, did not arrest in G1 and did not induce pheromone-specific genes at the restrictive temperature.